Hydrocephalus in Patients with Neurofibromatosis Type 1: MR Imaging Findings and the Outcome of Endoscopic Third Ventriculostomy - (:unkn) unknown (AMER SOC NEURORADIOLOGY, 2011)
Although hydrocephalus associated with NF-1 is not rare, up to now the MR imaging findings in these patients and the role of ETV in the treatment of hydrocephalus associated with NF-1 have not been investigated thoroughly. We present the MR imaging findings of hydrocephalus associated with NF-1 in 7 of 54 patients with NF-1. Although the types of obstruction were various, including aqueductal web, superior velum medullary synechia, periaqueductal/tectal hamartomas, cerebellar and pontine tegmentum hamartomas, brain stem glioma, or a combination, the presence of hamartomas was a consistent finding in patients with NF-1 with hydrocephalus. In 5 cases, 8 ETV procedures were performed and followed for up to 53 months. All children treated with ETV were shunt-free at their most recent examinations. ETV may be the primary procedure for the treatment of hydrocephalus associated with NF-1, regardless of the cause and the level of the obstruction.
Keywords: AQUEDUCTAL STENOSIS; CHILDREN; BRAIN; SPECTROSCOPY; ASSOCIATION